Canal wall-down procedure with soft posterior meatal wall reconstruction in acquired cholesteatoma: focus on postoperative middle ear status*. (3rd August 2018) - Tachibana, Tomoyasu; Kariya, Shin; Orita, Yorihisa; Nakada, Michihiro; Makino, Takuma; Komatsubara, Yasutoshi; Matsuyama, Yuko; Naoi, Yuto; Nishizaki, Kazunori
Abstract: Objectives: We reviewed surgical results of canal wall-down tympanoplasty (CWDT) with soft posterior meatal wall reconstruction (SWR) for acquired cholesteatoma (AC), and identified factors associated with surgical outcomes. Methods: Results from 119 ears with AC (pars flaccida, n = 99; pars tensa, n = 20) that underwent CWDT with SWR were retrospectively reviewed. We defined postoperative balloon-like retraction (PBR) with web formation, which needed reoperation to clean accumulated cerumen, as postoperative deep retraction pocket (PDRP). Results: Residual cholesteatoma was found in 11 ears (9.2%). Seven residual cholesteatomas were treated with outpatient operation. Seven ears (5.9%) showed PDRP. A transcanal approach was applied to all PDRPs. Postoperative mastoid reaeration was observed in 57 ears (47.9%). No factors significantly associated with residual cholesteatoma or PDRP were identified. The frequency of postoperative mastoid reaeration was significantly higher among cases with young age (<50 years), stage I cholesteatoma, or type I ossiculoplasty. Conclusion: CWDT with SWR showed low rates of residual cholesteatoma or postoperative deep retraction pocket (PDRP). Most residual cholesteatomas and PDRPs could be dealt with using a minimally invasive procedure. Young age, stage I cholesteatoma, and type I ossiculoplasty were associated with postoperative mastoid reaeration. This procedure seems fully feasible for surgical treatment of AC.